Dzieje Izraela (Mdr 10–19) jako objawienie Bożej sprawiedliwości w świetle dygresji z Mdr 12,12-22 - Demitrów, Andrzej (Verbum Vitae, 2014)
The Book of Wisdom is one of those late biblical Judaism texts that were created in the context of the creative confrontation with the Hellenic culture prevailing at that time. This confrontation concerned, among others, the basic question of faith of the chosen people, namely, the profession of the one only God who manifests his justice in the events of national and universal history. The basic event for the author of the Book of Wisdom is the exodus of Israel from Egypt, the aim of which was the entry of the chosen people into the Promised Land. On this way the nation experienced Godʼs Justice that proved to be his Grace and Mercy.